Volume 3: Heat Transfer, Parts a and B 2009
DOI: 10.1115/gt2009-59965
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Flow Instabilities Near the Rim Cavity of a 1.5 Stage Gas Turbine

Abstract: The present paper gives a contribution to a better understanding of the flow at the rim and in the wheel space of gas turbines. Steady state and time-accurate numerical simulations with a commercial Navier-Stokes solver for a 1.5 stage turbine similar to the model treated in the European Research Project ICAS-GT were conducted. In the framework of a numerical analysis, a validation with experimental results of the test rig at the Technical University of Aachen will be given. In preceding numerical investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 0 publications
3
22
0
1
Order By: Relevance
“…For an unconstrained flow with uniform density, the instability will apply to any shear layer. Computations with circumferentially uniform imposed annulus flow indicate that the high shear between purge and annulus flows support the occurrence of such instability [43,49]. Further to this Savov et al [34] associated increased unsteadiness in their seal outer cavity or trough with increased shear between purge and main annulus flows at off design conditions.…”
Section: Instability and Wave Theorymentioning
confidence: 91%
See 2 more Smart Citations
“…For an unconstrained flow with uniform density, the instability will apply to any shear layer. Computations with circumferentially uniform imposed annulus flow indicate that the high shear between purge and annulus flows support the occurrence of such instability [43,49]. Further to this Savov et al [34] associated increased unsteadiness in their seal outer cavity or trough with increased shear between purge and main annulus flows at off design conditions.…”
Section: Instability and Wave Theorymentioning
confidence: 91%
“…Amongst these are investigations by Rabs et al [43], and Zhang and Ma [44]. Rabs et al [43] performed URANS simulation on a 22.5 ∘ sector without vanes and blades.…”
Section: Axial Rim Sealsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chilla et al [2013] reported strong unsteady flow interaction between rim seal and main gas path at nominal sealing flow conditions, and periodically vortex shedding from rim seal into the main annulus. Rabs et al [2009] identified similar vertex structures and conjectured that they could be induced by the Kelvin-Helmholtz instabilities. The latest researches have all experimentally confirmed the existence of rim seal cavity modes which are unattributed to blade passing.…”
Section: Introductionmentioning
confidence: 99%
“…Rabs et al [32] performed unsteady simulations of a 1.5 stage turbine test rig with and without blades. The authors found that the introduction of a blade pressure field suppresses the Kelvin-Helmholtz type instabilities.…”
Section: Introductionmentioning
confidence: 99%